Peningkatan Kedisiplinan, Motivasi, Kompetensi, Pelatihan Manajemen Keuangan, Literasi Perencanaan Keuangan dan Perlindungan Guru dalam Pembentukan Budaya Organisasi di Yayasan Mutakabbir Kabupaten Bogor - Muhammad Rizal Saragih; Rusdi Rusdi; Dinar Ambarita; Prima Sadewa; Mawardi Nurullah; Julian Muhammad Hasan; Liana Dwi Septiningrum; Eka Rima Prasetya; Moh. Yuddy Yudawirawan; Dewi Ulfah Arini; Sujarwo Sujarwo; Muslim Muslim; Fery Citra Febriyanto; Eko Sasongko Priyadi; Diantia Amendy (Jurnal PKM Manajemen Bisnis, 2026)
Organizational culture within educational institutions plays a vital role in shaping the behavior, professionalism, and performance of educators and students alike. Yayasan Mutakabbir in Bogor Regency has identified key challenges related to discipline, motivation, competency, financial management, and the protection of teachers as part of its organizational development. To address these issues, a Community Service Program (PKM) titled "Improving Discipline, Motivation, Competence, Financial Management Training, Financial Planning Literacy, and Teacher Protection in Building Organizational Culture at Yayasan Mutakabbir" was conducted. The activity took place on May 28, 2025, involving 15 lecturers from the Bachelor of Accounting Program, Universitas Pamulang, as facilitators. The participants consisted of 50 individuals, including both students and teachers of Yayasan Mutakabbir. The PKM was implemented using a knowledge-sharing method combined with interactive Q&A sessions, ensuring participant engagement and practical understanding. The program was carried out in three main stages: preparation, implementation, and reporting. Topics delivered included discipline building, motivation enhancement, basic financial management, financial planning, and strategies for safeguarding teacher rights. The outcomes of this program demonstrated increased awareness, improved knowledge, and positive behavioral shifts among participants, particularly in terms of financial literacy and organizational values. This activity has laid a strong foundation for the development of a more professional and values-oriented organizational culture within Yayasan Mutakabbir.